Intensive Management of A 21-Year-Old Male Patient with Acute Respiratory Failure Due to Near Drowning: A Case Report - Liliriawati Ananta Kahar; Kornelis Aribowo; Clarissa Hasana Hasmi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The mechanism of near drowning involves decreased lung compliance and aspiration of water into the lungs, which damages surfactants and disrupts alveolar capillary membranes. This leads to the development of alveolar oedema, and ventilation-perfusion mismatch, which causes hypoxemia leading to acute respiratory distress syndrome (ARDS) and cause other organ dysfunction and death. Case presentation: The patient was found drowned by his friends while on vacation and swimming in the river. Initial physical examination in the ED obtained a Glasglow coma scale (GCS) score of 14/15 (E3-V5-M6), blood pressure 124/70 mmHg, and pulse 124 beats/min. The patient breathed spontaneously 25 breaths/min with oxygen saturation (SpO2) of 90% on room air. The patient was initially managed with oxygenation using a non-rebreathing mask (NRM semi-fowler positioning and peripheral access. Chest X-ray and other radiologic examinations, including a brain CT scan, were performed before the patient was immediately transferred to the ICU, and there was no evidence of other trauma. During the 9 days of intensive management in the ICU, there was a good improvement from GCS 14 to 15. Conclusion: Intensive management of a 21-year-old male patient with acute respiratory failure due to near drowning.